2016
DOI: 10.1111/adb.12385
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mitragynine (kratom) enhances punishment resistance in natural reward seeking and impairs place learning in mice

Abstract: Kratom (Mitragyna speciosa) is a widely abused herbal drug preparation in Southeast Asia. It is often consumed as a substitute for heroin, but imposing itself unknown harms and addictive burdens. Mitragynine is the major psychostimulant constituent of kratom that has recently been reported to induce morphine-like behavioural and cognitive effects in rodents. The effects of chronic consumption on non-drug related behaviours are still unclear. In the present study, we investigated the effects of chronic mitragyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 46 publications
2
39
0
2
Order By: Relevance
“…There have been different studies linking M.speciosa preparation and mitragynine administration with elevated blood pressure, hepatotoxicity, and nephrotoxicity effects in rats (Harizal, Mansor, Hasnan, Tharakan, & Abdullah, 2010). Impaired cognitive behavioural function (Apryani, Hidayat, Moklas, Fakurazi, & Idayu, 2010;Ismail, Jayabalan, Mansor, Müller, & Muzaimi, 2017;Yusoff et al, 2014), unpleasant withdrawal symptoms (Yusoff et al, 2014), and toxicity and mortality incidences have been reported in humans (Singh et al, 2016).…”
Section: Effects and Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been different studies linking M.speciosa preparation and mitragynine administration with elevated blood pressure, hepatotoxicity, and nephrotoxicity effects in rats (Harizal, Mansor, Hasnan, Tharakan, & Abdullah, 2010). Impaired cognitive behavioural function (Apryani, Hidayat, Moklas, Fakurazi, & Idayu, 2010;Ismail, Jayabalan, Mansor, Müller, & Muzaimi, 2017;Yusoff et al, 2014), unpleasant withdrawal symptoms (Yusoff et al, 2014), and toxicity and mortality incidences have been reported in humans (Singh et al, 2016).…”
Section: Effects and Side Effectsmentioning
confidence: 99%
“…Acute administration of mitragynine produces anxiolytic-like effects attributed to the interactions among opioidergic receptor systems (Hazim, Ramanathan, Parthasarathy, & Muzaimi, 2014). Findings from animal studies have indicated that M.speciosa is toxic and may cause lethal effects at higher doses (Hassan et al, 2013;Ismail et al, 2017). Recent findings from a Poison Centre in Thailand recorded 52 kratom exposure cases that were reported to the Centre's surveillance system from 2005 to 2009.…”
Section: Ketum Toxicitymentioning
confidence: 99%
“…; Ismail et al . ). Moreover, MG and 7‐HMG fully generalize to the discriminative stimulus effects of morphine, suggesting the potential for abuse (Harun et al, ).…”
Section: Introductionmentioning
confidence: 97%
“…Concern of potential abuse is expressed because low doses act as a stimulant and therefore might pose the risk of a milder version of the stimulation produced by amphetamines or cocaine, and higher doses produce more sedative effects, possibly posing the risk of a milder version of opioids [56][57][58]. In some preclinical studies, mitragynine has been reported to be mildly rewarding, or to impair learning and memory [51,59,60]. But recent studies have shown that mitragynine is not self-administered by rats [61,62].…”
Section: Abuse Potentialmentioning
confidence: 99%